The poetry of Bienvenido N. Santos a stylistic analysis - Marcial, Ma. Corazon P. (Quezon City College of Arts and Letters, University of the Philippines Diliman, 1989)
This paper is an attempt to do a stylistic analysis of the poetry of Bienvenido N. Santos. two interrelated stylistic devices, cohesion and foregrounding, are the main concern of this paper.Ten poems by Santos are used in the analysis. Stylistic analysis, specifically cohesion and foregrounding, is an effective method in literary analysis in the same manner that the poetry of B. N. Santos is suitable for said type of approach.
Thesis (B.A. in English)--University of the Philippines Diliman
Includes bibliographical references.